Light-responsive polymers for microfluidic applications. Issue 5 (12th February 2018) - ter Schiphorst, Jeroen; Saez, Janire; Diamond, Dermot; Benito-Lopez, Fernando; Schenning, Albertus P. H. J.
Abstract : Light responsive polymers will drive revolutionary changes in microfluidics by reducing costs, platform dimensions and complexity. Abstract : While the microfluidic device itself may be small, often the equipment required to control fluidics in the chip unit is large e.g. pumps, valves and mixing units, which can severely limit practical use and functional scalability. In addition, components associated with fluidic control of the device, more specifically the valves and pumps, contribute significantly to the overall unit cost. Here we sketch the problem of a gap between high end accurate, but expensive sensor platforms, versus less accurate, but widely employable hand-held low-cost devices. Recent research has shown that the integration of light-responsive materials within microfluidic devices can provide the function of expensive fluidic components, and potentially enable sophisticated measurements to be made using much less expensive equipment. An overview of the most recent developments will be presented for valves, mixers, transport and sample handling inside microfluidic devices.